Effect of Acupressure and Abdominal Massage on Constipation in Patients with Total Knee Arthroplasty: A Randomized Controlled Study - Durmuş İskender, Mahinur; Çalışkan, Nurcan (SAGE Publications, 2021)
This study was a randomized controlled trial aimed to compare the effects of acupressure and abdominal massage on constipation development for patients with TKA. The patients were randomly assigned to each group: control group ( n = 31), acupressure group ( n = 30), and abdominal massage group ( n = 30). The finding showed that the severity of constipation and straining stool consistency of the groups in which acupressure and abdominal massage was applied are significantly better than the control group ( p < .05). When the first defecation times of the groups are analyzed, it is seen that the patients to whom acupressure and abdominal massage are applied defecate significantly earlier than the control group ( p < .05). It has been concluded that safe non-invasive acupressure and abdominal massage that can be easily applied by health professions, healthy individuals, and patients is effective on patients with total knee arthroplasty for the prevention of constipation.
Keywords: Massage; Research Design; Humans; Acupressure; Arthroplasty, Replacement, Knee; Constipation; 3. Good health